ANALISIS BUDAYA KERJA SAMAPTA RUMEKSA PADA BENGKEL SENJATA FASHARKAN LANTAMAL V SURABAYA - jurnalpps pps; Aries Hermawan; Indra Prasetyo; C. Sri Hartati (Prodi Magister Manajemen Universitas Wijaya Putra, 2018)
This study aims to describe the Surabaya Lantamal V Fasharkan Weapons Workshop which has a strategic function in an effort to support the maintenance and repair of weapons in the Navy. The type of research used is a descriptive approach and this research approach is a qualitative approach. The location of the study was Surabaya's Lantamal V Fasharkan Weapon Workshop. Data analysis techniques are qualitative descriptive data analysis techniques. Internal factors in the application of Samapta rumeksa's work culture include the limited number of personnel and the number of experts, limited spare parts. External factors include limited SOPs and manuals, limited list of personnel, limited facilities and infrastructure, limited personnel training, limited budgets, limited repairs. Then as an internal supporting factor which includes the level of formal education of members and members of the Weapons Workshop, the souls of officers, service experience, motivation of superiors, skills and training, as well as good cooperation and the availability of modern equipment. External supporting factors are site preparation, provision of facilities and infrastructure, provision of SOP and manual books. Keywords: work culture, Trisila Indonesian Navy, standard operating procedure